The Intergenerational Transmission of Human Capital. The Role of Skills and Health - Petter Lundborg; Martin Nordin; Dan-Olof Rooth (Lund University, School of Economics and Management, Department of Economics, 2012)
We provide new evidence on the causal mechanisms reflected in the intergenerational transmission of human capital. Applying both an adoption and a twin design to rich data from the Swedish military enlistment, we show that greater parental education increases son's cognitive and non-cognitive skills, as well as their health. The estimates are in many cases similar across research designs and suggest that a substantial part of the effect of parental education on the children's education works through improving children's skills and health.
Keywords: C41; I11; I12; J12; J14; 330; Intergenerational Transmission; Human Capital; Education; Health